Impact of comorbidities, diabetes, and smoking on sustained outcomes in rheumatoid arthritis: a retrospective study - Zhaklin Apostolova; Tanya Shivacheva; Tsvetoslav Georgiev (Rheumatology)
Introduction Rheumatoid arthritis (RA) is a chronic autoimmune disease significantly impacting patients’ quality of life (QoL) and necessitating complex, long-term treatment. This study aimed to assess the long-term therapeutic outcomes of biologic therapies in a real-world clinical setting, focusing on the achievement and maintenance of low disease activity (LDA) among RA patients, while also investigating factors influencing these outcomes.